The Influence of Competence, Compensation, Organizational Commitment, Training and Working Experience On Employee Performance - Hadi Purnomo; Tri Melda Mei Liana; Sunday Ade Sitorus; Lasma Lenida Rosinta Sianipar; Ronny Allan Nababan; Mazzlida Mat Deli; SUNDAY ADE SITORUS (Yayasan Riset dan Pengembangan Intelektual, 2023)
Research on analyzing the influence of competence, compensation, organizational commitment, training, and work experience is used as a test of employee performance. The population in this research process is all employees of PT XYZ. In this clai research, data sampling techniques will be used with a combined method of area sampling techniques and also simple random sampling with a population of employees from PT XYZ. Analysis of this data itself shows several factors such as compensation, competence and also organizational commitment that have a simultaneous and significant influence on the performance of employees of PT XYZ. Then the role of competencies that have a very significant role on the performance and satisfaction of employees who work at PT XYZ. This research was conducted to analyze various factors that have an influence on the motivation of employees and also the performance of employees at PT XYZ. The data analyzed is data related to compensation and competencies that can have an influence on employees in terms of compensation, competence and motivation. From the data obtained, PT XYZ must provide compensation, competence to employees in order to improve their performance.